Large shareholder ownership types and board governance - Ho, Joanna; Huang, Cheng Jen; Karuna, Christo (Journal of Corporate Finance, 2020)
ABSTRACTbstract This study examines the relation between large shareholder ownership and board governance in firms. Using a dataset comprising Taiwanese firms, we find that different types of large shareholder ownership influence board governance in different ways. Specifically, we find that greater family ownership is associated with greater outside director proportion on the board and a higher likelihood of CEO-chair combination. The nature of the relation between institutional ownership and board governance depends on whether the institutional owners are foreign or domestic, and active or passive. Our findings collectively suggest that family (institutional) ownership is more associated with an advisory (monitoring) board. Our study contributes to the literature by providing evidence on the multidimensional nature of the relation between large shareholder ownership types and board governance.